Theoretical Foundations Of Private Entrepreneurship's Economic Security - Nabijonovna, Bayboboeva Firuza (Antis Publisher, 2024)
In this article, we emphasize the need for the state to support and regulate entrepreneurship in the field of logistics, information, technology, consulting, marketing, educational services, financial support and other areas. One of the main features of small business and private entrepreneurship is that this sector of the economy needs constant state support.